Production of Cross-Linked Resistant Starch From Tapioca Starch and Effect of Reaction Conditions on the Functional Properties, Morphology, X-Ray Pattern, Ft-Ir Spectra and Digestibility - Korkut, Ayse; Kahraman, Kevser (Springer, 2021)
The aim of this study was to investigate the effect of cross-linking temperature and pH on resistant starch (RS) formation as well as the functional, structural and morphology properties of tapioca starch. Tapioca starch was cross-linked using sodium trimetaphosphate (STMP) and sodium tripolyphosphate (STPP) at various temperature and pH. Increase in the reaction temperature and pH increased RS content and decreased swelling power (SP) of the samples. The sample cross-linked at 60 degrees C and pH 12 had the highest RS content (84.8%) and the lowest SP (3.0 g/g). The correlation coefficient between RS content and SP was 0.96. Cross-linking altered the pasting behavior significantly, while Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) patterns changed slightly. Cross-linking did not change the morphological structure and granular shape of the starch. In addition, cross-linked samples protect their original shapes during cooking and in vitro digestion probably since cross-linking restrict the water uptake and swelling due to the increase in the bonds within the molecule. Overall results proved that cross-linking at high temperature and high alkaline condition resulted in an increase in the RS content of tapioca starch.
Kahraman, Kevser/0000-0002-2786-3944;
Keywords: Cross-Linking; Tapioca Starch; Sem; Xrd; Ft-Ir; In Vitro Digestion